Immunogenicity of hypothetical highly conserved proteins as novel antigens in Anaplasma marginale - Nuñez, Pablo Alfredo; Moretta, Rosalia Ester; Ruybal, Paula; Wilkowsky, Silvina Elizabeth; Farber, Marisa Diana (Springer, 2019)
Anaplasma marginale is a tick-transmitted Gram-negative intraerythrocytic bacterium and the etiological agent of bovine Anaplasmosis. Even though considerable research efforts have been undertaken, Anaplasmosis vaccine development remains a challenging field. Outer-membrane-specific antigens responsible for the ability of more complex immunogens could have a significant role in the protective response. Thus, the identification of outer-membrane antigens represents a major goal in the development of bacterial vaccines. Considering that 40 % of the annotated proteins in A. marginale remain as hypothetical, we selected three candidate antigens, AM1108, AM127, and AM216 based on experimental evidence, in silico structure prediction of β-barrel outer membrane, and orthology clustering. Sequence alignment and analysis demonstrated a high degree of conservation for the three proteins between the isolates from Argentina compared to the American strains. We confirmed the transcription of the three genes in the intraerythrocytic stage. AM1108 and AM216 recombinant proteins elicited specific T-cell response proliferation and a significant rise in TNF-α and IFN-γ transcript levels, respectively. Only AM1108 was able to be recognized by specific antibodies from infected bovines. This study allowed the identification of new candidate components of the outer-membrane fraction of A. marginale. Further studies will be required to analyze their potential as effective antigens for being included in rational vaccine strategies.